1127 APPLICABILITY OF THE EXCEL TRIAL CRITERIA IN AN ALL-COMERS REAL-WORLD POPULATION OF UNPROTECTED LEFT MAIN PCI. (15th December 2022) - Castaldi, Gianluca; Benedetti, Alice; Zivelonghi, Carlo; Buongiorno, Antonia Luisa; Vermeersch, Paul; Agostoni, Pierfrancesco
Abstract: Background: The Evaluation of XIENCE versus Coronary Artery Bypass Surgery for Effectiveness of Left Main Revascularization (EXCEL) trial is the largest randomized trial comparing percutaneous coronary intervention (PCI) with 2nd generation drug eluting stents (DES) and bypass surgery in unprotected left main disease (ULMD). Our aim was to assess which proportion of patients from a contemporary all-comers population of ULMD-PCI would be eligible for the EXCEL trial and whether these patients showed different short- and long-term outcomes than the rest of the population. Methods and results: A total of 246 consecutive patients that underwent ULMD-PCI between January 2018 and December 2021, were retrospectively analyzed. After application of the EXCEL trial inclusion ed exclusion criteria, 98 patients (38.9%) were allocated in the "Excel-like" cohort and 148 in the "Non-Excel-like". Baseline characteristics of the two groups were substantially comparable. Mean baseline Syntax Score (SS) was significantly lower in the "Excel-like" patients (Excel 20.1 ± 7.1 VS Non-Excel 23.0 ± 11.2; p-value = 0.025) than the "Non-Excel-like" group with the latter showing also a higher degree of incomplete revascularization (rSS >8: Excel 11.2%.VS Non-Excel 25.7%; p-value 0.005). At 1 year the cumulative major adverse cardiovascular and cerebral events (MACCEs) rates were 7.2% and 17.2% for the "Excel-like" and "Non-Excel-like" patients respectively (Log-rank p-value = 0.03). At last follow-up available the significant difference in MACCEs rate persisted (Excel 19.3%, VS Non-Excel 37%, Log-rank p-value 0.02) and a significant difference in any unplanned revascularization was also shown (Excel 1.5% VS Non-Excel 12.6%; p-value 0.04). Conclusions: in a contemporary real-world cohort of ULMD-PCI only a minority of the patients could be enrolled in the EXCEL trial. This cohort of patients showed a more extensive revascularization and less clinical events at long-term follow-up despite comparable burden of cardiovascular risk factors and atherosclerotic coronary disease. These findings "challenge" the external applicability of the results of the Excel trial in the routine clinical activity.